Synbiotic microcapsule dietary supplementation for prevention against co-infection diseases in Pacific white shrimp: a limited field experiment - Munti Yuhana; Tambun, Andreas; Widanarni, Widanarni; Afiff, Usamah (Indonesian Society of Scientific Aquaculture (ISSA), 2022)
This study aimed to evaluate the effectivity of microencapsulated synbiotic (MS), Bacillus sp. NP5 and mannan oligosaccharide (MOS) dietary in different feeding frequencies in Pacific white shrimp culture field experiment. The MS was administered as a feed supplementation to enhance the immunity for prevention against co-infection with WSSV (White Spot Syndrome Virus) and Vibrio harveyi. The synbiotic was microencapsulated by the spray dryer method. Shrimps were reared in the floating net cages in the pond. Treatments included the administration of MS at different frequencies i.e, daily (A), twice a week (B), once a week (C), and without MS supplementation (consisted of negative and positive controls) with a feeding rate of 6% of shrimp biomass (5 times a day). During the challenge trial, shrimps were removed and further reared in plastic tanks, for 7 days. The shrimps (except negative control treatment) were intramuscularly injected by WSSV filtrate at the infective dosage of 10-4 copies.ml-1. Twenty four hours after WSSV injection the shrimps were immersed in the water-containing cells suspension of V. harveyi at the cell’s population dosage of 106 CFU.ml-1. Immune responses were observed for 7 days after experimental infection. The shrimps that have been treated with daily MS supplementation (A) showed better immune responses i.e., total haemocyte counts, phenoloxidase, respiratory burst, and the lower pathogenic cells abundance in the intestine compared to other treatments groups.